HiL Ground Fault Distance Protection Tests of Novel Zero Sequence Control VSC - Löbel, Jonathan; Mahr, Florian; Jäger, Johann (2024 IEEE Power & Energy Society General Meeting (PESGM), 2024)
The number of power electronic converters in the electrical grid is increasing. In converter dominated grids, these determine the fault behaviour of the grid significantly. This behaviour mostly deviates from the classic fault behaviour in the case of synchronous machine dominating grids. In addition novel converter control schemes provide exemplary an unconventional fault behaviour regarding the zero sequence fault currents. In order to ensure the protection security and dependability in the future under these circumstances, protection relays and algorithms must be tested for this new behaviour preferably in real time.This paper presents a distance protection relay hardware-in-the-loop setup for real-time tests. Ground faults in the presence of a novel converter control scheme for zero sequence fault currents and various conventional distance protection algorithms were investigated. The novel converter topology enables zero sequence current control during ground faults using a virtual impedance. The protection relay response is based on the transient or steady state phases of the fault current which are adjustable in terms of magnitude, angle and duration. The test case show, that purely current-based pickup methods do not lead to fault detection because of current limitation of the converter. With all other tested methods, the ground fault was detected correctly. The test results are the basis of an optimal adjustment of the zero sequence current control of the converter to a proper protection relay respons